2022
DOI: 10.1590/1679-78256835
|View full text |Cite
|
Sign up to set email alerts
|

Preformed Fragment Velocity Distribution of Elliptical Cross-section Projectile

Abstract: In the field of warhead design, non-cylindrical warhead, especially elliptical cross-section warhead, has received considerable attention. In this study, the initial velocity and distribution characteristics of the preformed fragments of a columnar projectile with an elliptical cross-section were examined. To obtain the velocity distribution of the fragments in this kind of projectile, three elliptical cross-section projectiles with different geometric sizes were test based on the static detonation tests. Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…D-shaped charge refers to the charge structure whose cross section has the shape of the letter 'D', which can achieve a higher gain of damage energy in the aim direction through the optimisation of the structural design and initiation mode [3]. Deng et al found that an oval charge structure had a fragment focusing effect in the direction of the minor axis of the oval [4]. As indicated by these studies, the occurrence scenes of the explosion damage and fragment dispersion property of non-axisymmetric shells have gradually become common.…”
Section: Introductionmentioning
confidence: 99%
“…D-shaped charge refers to the charge structure whose cross section has the shape of the letter 'D', which can achieve a higher gain of damage energy in the aim direction through the optimisation of the structural design and initiation mode [3]. Deng et al found that an oval charge structure had a fragment focusing effect in the direction of the minor axis of the oval [4]. As indicated by these studies, the occurrence scenes of the explosion damage and fragment dispersion property of non-axisymmetric shells have gradually become common.…”
Section: Introductionmentioning
confidence: 99%